The 2022 Seismic Hazard Model for Costa Rica - Hidalgo Leiva, Diego Antonio (2023)
Costa Rica is located at the boundary of four tectonic plates where the regularity of destruc tive earthquakes highlights the necessity of seismic hazard estimations. This study contains the most recent Probabilistic Seismic Hazard Assessment (PSHA) for Costa Rica, calculated with the largest and the most updated earthquake database from both—the Earthquake Engineering Laboratory and the National Seismological Network of the University of Costa Rica. For the PSHA, we updated the seismicity parameters for the upper plate, sub duction interplate, and intraslab tectonic domains, characterized the upper-plate zones by percentages of fault types, and used weighted ground-motion models for each of the tec tonic domains. The resulted maps of peak ground acceleration (PGA) at return periods of 475 yr (PGA-475) and 2475 yr, as well as the spectral accelerations, show geographic trends that allow for the division of the country in four seismic hazard levels: (1) extremely high for the Nicoya, Osa, and Burica peninsulas, situated directly above the subduction interplate, where the PGA-475 could be 0.55–1.20g; (2) very high for most of the Guanacaste Province, where the PGA-475 may be 0.55–0.70g; (3) high for most of the country ( ∼41%) with PGA-475 values of 0.40–0.55g, including Central Costa Rica and the capital city of San Jose; and (4) moderate for the Talamanca Cordillera and Northern Costa Rica, with PGA-475 up to 0.40g. These ground-motion values are 0.1–0.6g higher than the previous PSHA for the Pacific peninsulas, Guanacaste, and the southeastern Caribbean. Further, hazard curves, uni form hazard spectra, and a hazard disaggregation indicate that the seismic hazard is lower but more complex in San Jose than in Liberia—the largest city in Guanacaste.